Efeito da variação do feedback e da possibilidade de repetição de itens incorretos no desempenho em uma Instrução Programada - Pieretti, Ana Alice Reis (2015)
In spite of the existence of a fair amount of studies on programmed instruction, previously reported findings show some inconsistencies, and some specific manipulations in the implementation of this technology of teaching have not been satisfactorily investigated yet. The current study assessed the influence of varying the opportunities for receiving feedback as well as the influence of the moment of repetition of items answered incorrectly on learning under a programmed instruction procedure. Sixteen students, divided into two groups, participated in this study. All participants were given a pretest, training and a posttest. However, the conditions described below were manipulated only during the training session. Group 1 was exposed to the varied opportunities of repetition of those frames answered incorrectly under the following conditions: 1a) Repetition at the end of the series only once; 1b) Repetition at the end of the series up to three times; 1c) Repetition after feedback only once; 1d) Repetition after feedback up to three times. A procedure that varied the type of feedback was adopted for Group 2, in accordance with the following conditions: 2e) Feedback after every answered frame; 2f) No feedback for any of the answered frames; 2g) Feedback for every frame answered correctly; 2h) Feedback after every incorrectly answered frame. Results showed that all participants produced a higher percentage of correct posttest answers compared to pretest answers. The highest average percentages occurred in the Repetition after feedback up to three times condition (67.42% correct answers) and the Repetition after feedback only once condition (66.06% correct answers). As for Group 2, the conditions with the highest average percentages for correct answers were Feedback after every frame (69.5%) and Feedback after every incorrectly answered frame (69.2%). The influence of the implementation of the whole procedure in only one session on participants posttest performance is discussed. Furthermore, it is possible to claim that the moment when repetition of items occurred seemed to have exerted more influence on participants performance than the amount of times they could repeat the item answered incorrectly. It is also warranted a discussion about the need for increasing the number of opportunities for repeating the incorrect items